APPLICATION OF NORDIC WALKING IN REHABILITATION OF CARDIOLOGY PATIENTS - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii)
The consequences of diseases of the cardiovascular system are currently socially significant, which is associated with a high level of disability, disability and mortality of the population. The development of methodological approaches to the organization of rehabilitation of patients with diseases of the cardiovascular system with the use of effective means of kinetotherapy of aerobic orientation seems relevant. Nordic walking as a means of cardiac rehabilitation allows solving a wide range of therapeutic and preventive tasks. The article presents the results of the study to identify the effectiveness of the application of a complex kinetotherapeutic rehabilitation program with the inclusion of Nordic walking for persons with diseases of the cardiovascular system at the polyclinic stage. To evaluate the effectiveness of the developed rehabilitation program, functional assessment methods were used: the 6-min walk test, the Rufier test and treadmill stress testing. Keywords: cardiovascular diseases,physiotherapy, physical rehabilitation, Nordic walking, tolerance to physical activity, quality of life.